Differentiating Delirium From Sedative/Hypnotic-Related Iatrogenic Withdrawal Syndrome: Lack of Specificity in Pediatric Critical Care Assessment Tools*. Issue 6 (June 2017) - Madden, Kate; Burns, Michele M.; Tasker, Robert C.
Abstract : Objectives: To identify available assessment tools for sedative/hypnotic iatrogenic withdrawal syndrome and delirium in PICU patients, the evidence supporting their use, and describe areas of overlap between the components of these tools and the symptoms of anticholinergic burden in children. Data Sources: Studies were identified using PubMed and EMBASE from the earliest available date until July 3, 2016, using a combination of MeSH terms "delirium, " "substance withdrawal syndrome, " and key words "opioids, " "benzodiazepines, " "critical illness, " "ICU, " and "intensive care." Review article references were also searched. Study Selection: Human studies reporting assessment of delirium or iatrogenic withdrawal syndrome in children 0–18 years undergoing critical care. Non-English language, exclusively adult, and neonatal intensive care studies were excluded. Data Extraction: References cataloged by study type, population, and screening process. Data Synthesis: Iatrogenic withdrawal syndrome and delirium are both prevalent in the PICU population. Commonly used scales for delirium and iatrogenic withdrawal syndrome assess signs and symptoms in the motor, behavior, and state domains, and exhibit considerable overlap. In addition, signs and symptoms of an anticholinergic toxidrome (a risk associated with some common PICU medications) overlap with components of these scales, specifically in motor, cardiovascular, and psychiatric domains. Conclusions: Although important studies have demonstrated apparent high prevalence of iatrogenic withdrawal syndrome and delirium in the PICU population, the overlap in these scoring systems presents potential difficulty in distinguishing syndromes, both clinically and for research purposes. Abstract : Supplemental Digital Content is available in the text.